Factors related to the formation of buccal mucosa ridging in university students. (January 2014) - Mizutani, Shinsuke; Ekuni, Daisuke; Tomofuji, Takaaki; Azuma, Tetsuji; Irie, Koichiro; Machida, Tatsuya; Yoneda, Toshiki; Iwasaki, Yoshiaki; Morita, Manabu
Abstract Objective. Buccal mucosa ridging (BMR) is known as a clinical sign of clenching, which is one of the major manifestations of bruxism. However, there are few reports about the formation of BMR and no data regarding the association between BMR and factors such as malocclusion. The purpose of the current study was to investigate the relationship between BMR and factors such as the number of teeth present, gender, body mass index (BMI), occlusion and clenching habit in university students. Materials and methods. A total of 2101 students (1164 males, 937 females), aged 18–29 years old, were included in the study. BMR and the number of teeth present were recorded and malocclusion was defined using a modified version of the Index of Orthodontic Treatment Need. Additional information regarding gender, clenching habit and BMI was collected via a questionnaire. Results. Forty-six per cent of the subjects had BMR and the prevalence of BMR in females was significantly higher than that of males (chi square test, p < 0.001). According to logistic regression analysis, the probability of BMR was significantly associated with female gender (OR = 1.501, 95% CI = 1.259–1.790, p < 0.001), crowding (OR = 2.102, 95% CI = 1.706–2.590, p < 0.001) and overjet (OR = 0.585, 95% CI = 0.418–0.818, p = 0.002). On the other hand, BMR was not associated with awareness of clenching habit and BMI. Conclusions. Gender, crowding and overjet were related to the formation of BMR in university students. When evaluating BMR as a clinical sign of clenching, one might have to take factors such as gender and crowding into consideration.